4(r+6)+36=2(2r+40)

Simple and best practice solution for 4(r+6)+36=2(2r+40) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(r+6)+36=2(2r+40) equation:


Simplifying
4(r + 6) + 36 = 2(2r + 40)

Reorder the terms:
4(6 + r) + 36 = 2(2r + 40)
(6 * 4 + r * 4) + 36 = 2(2r + 40)
(24 + 4r) + 36 = 2(2r + 40)

Reorder the terms:
24 + 36 + 4r = 2(2r + 40)

Combine like terms: 24 + 36 = 60
60 + 4r = 2(2r + 40)

Reorder the terms:
60 + 4r = 2(40 + 2r)
60 + 4r = (40 * 2 + 2r * 2)
60 + 4r = (80 + 4r)

Add '-4r' to each side of the equation.
60 + 4r + -4r = 80 + 4r + -4r

Combine like terms: 4r + -4r = 0
60 + 0 = 80 + 4r + -4r
60 = 80 + 4r + -4r

Combine like terms: 4r + -4r = 0
60 = 80 + 0
60 = 80

Solving
60 = 80

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8j-5=46 | | 60+50.45x=0+57.95 | | 9+4x=428 | | 7y-15=-1 | | y-9=-5(x+6) | | 3(9y+3)-11=2y+21 | | -6X+-36=-6x+-3 | | 2x+(3+4)=52 | | ax+d=c-bx | | 60n=(-12) | | -6X+36+2=-6x+-3 | | x+b=c-z | | 9a-(-72)=-8 | | -6=3y-21 | | 4k=-2k+18 | | 8=cups | | (0.25)X-1=32 | | 10e-6=14 | | 5.23x+10.46=20.92 | | 7+5x-3x=13 | | 9-3(2g+2)= | | 13x-17=9x-15 | | 12*5n=0 | | 40x-26x^2+4x^3=0 | | 2(4-3x)=8 | | x+20=52 | | y-36=7 | | 8(8-4)=-2(x+6) | | 8y-4y-5=61.84 | | 4(x+9)=30 | | -8=2v+4 | | 10X+14+8= |

Equations solver categories